2020
DOI: 10.1097/dss.0000000000002153
|View full text |Cite|
|
Sign up to set email alerts
|

Pooled Subject-Reported Outcomes From 2 Phase 3 Studies of OnabotulinumtoxinA for Simultaneous Treatment of Forehead and Glabellar Lines

Abstract: BACKGROUND Understanding the subjects' perspective is critical for successfully treating upper facial lines. OBJECTIVE To understand subjects' self-perception and overall satisfaction after onabotulinumtoxinA treatment for forehead and glabellar lines. METHODS This analysis pooled data from two 12-month, pivotal phase 3 studies in which toxin-naive subjects received onabotulinumtoxinA 40 U or placebo for tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…2,3 The most frequent areas targeted with neuromodulators include the forehead and the glabellar complex which has been shown to result in a younger overall facial appearance. 4 Recent anatomic research has reported on the bidirectional movement of the frontalis muscle providing evidence for two separate segments of this muscle: eyebrow elevator (lower forehead) vs hairline depressor (upper forehead). 5 To avoid eyebrow ptosis, the authors suggested injecting a reduced amount of neuromodulators in the eyebrow elevation segment of the frontalis muscle via a more superficial product administration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 The most frequent areas targeted with neuromodulators include the forehead and the glabellar complex which has been shown to result in a younger overall facial appearance. 4 Recent anatomic research has reported on the bidirectional movement of the frontalis muscle providing evidence for two separate segments of this muscle: eyebrow elevator (lower forehead) vs hairline depressor (upper forehead). 5 To avoid eyebrow ptosis, the authors suggested injecting a reduced amount of neuromodulators in the eyebrow elevation segment of the frontalis muscle via a more superficial product administration.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent areas targeted with neuromodulators include the forehead and the glabellar complex which has been shown to result in a younger overall facial appearance 4 . Recent anatomic research has reported on the bidirectional movement of the frontalis muscle providing evidence for two separate segments of this muscle: eyebrow elevator (lower forehead) vs hairline depressor (upper forehead) 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent publication of two 12-month, phase 3 studies of toxin-naive subjects receiving onabotulinumtoxinA or placebo for treatment of FHLs noted that the current versions of these questionnaires meet the FDA PRO guidance. 7 In these phase 3 studies, subject-reported satisfaction and impact of treatment were prespecified secondary endpoints collected from FLSQ and FLO-11. 7 Based on the evidence from these studies, the FDA approved FLSQ satisfaction data in the product labeling for onabotulinumtoxinA treatment of FHLs.…”
mentioning
confidence: 99%
“… 7 In these phase 3 studies, subject-reported satisfaction and impact of treatment were prespecified secondary endpoints collected from FLSQ and FLO-11. 7 Based on the evidence from these studies, the FDA approved FLSQ satisfaction data in the product labeling for onabotulinumtoxinA treatment of FHLs. 7 …”
mentioning
confidence: 99%
See 1 more Smart Citation